Small Vessel Disease Burden and Outcomes of Mechanical Thrombectomy in Ischemic Stroke: A Systematic Review and Meta-Analysis - Xu, Tao; Wang, You; Yuan, Jinxian; Chen, Yangmei; Luo, Haiyan (Frontiers in Neurology, 2021)
Background: Cerebral small vessel disease (SVD) is prevalent in the population, especially among elderly individuals. Substantial uncertainties remain about the clinical relevance of SVD with outcomes of mechanical thrombectomy (MT) in acute ischemic stroke (AIS). Objectives: This systematic review and meta-analysis was performed to evaluate the association between SVD and clinical outcomes in patients with AIS undergoing MT. Methods: We systematically searched the Medline, Embase, and Cochrane databases for relevant clinical studies. The exposure of SVD mainly included leukoaraiosis, cerebral microbleeds (CMBs), and lacunes. The pooled odds ratio (OR) was used to calculate the association between each subtype of SVD and outcomes of MT. The primary outcome was poor functional outcome, which was defined as a modified Rankin Scale score (mRS) ≥ 3 at 90 days after MT. The secondary outcomes included mortality at 90 days, in-hospital mortality, intracranial hemorrhage (ICH) and symptomatic intracranial hemorrhage (sICH), successful recanalization and futile recanalization (FR), early neurological improvement, and early neurological deterioration (END) after MT. Results: Overall, 20 studies with 5,189 patients with AIS undergoing MT were included. High leukoaraiosis burden (HLB) at baseline was associated with increased risks of poor functional outcome at 90 days (OR 2.70, 95% confidence intervals (CI) 2.01–3.63; p < 0.001; 10 studies; n = 2,004), in-hospital mortality (OR 4.06, 95% CI 1.48–11.13; p = 0.006; 2 studies; n = 314), FR (OR 5.00, 95% CI 2.86–8.73; p < 0.001; 3 studies; n = 493), and END (OR 2.65, 95% CI 1.09–6.45; 1 study; n = 273) after MT. HLB (VSS 3-4 or FS ≥ 2) at baseline was not associated with mortality at 90 days, ICH, or sICH after MT. CMBs at baseline were found to be associated with increased risks of poor functional outcome at 90 days (OR 1.84, 95% CI 1.17–2.90; p = 0.008; 2 studies; n = 1,924) after MT. We found no association between the presence of lacunes and poor functional outcome at 90 days after MT. Conclusions: In patients with AIS undergoing MT, HLB and CMBs were associated with increased risks of unfavorable outcomes after MT.